Some initial experimental results on the conditions of free water layer formation in horizontal pipes - Thien, Nguyen Duy; Diep, Nguyen Van; Hai, Duong Ngoc; Phan, Nguyen Hong (Vietnam Journal of Mechanics, 1999)
This paper presents an experimental facility conducted in Hanoi Institute of Mechanics to investigate multiphase How pattern in the pipes. First and foremost, it is used to define the conditions of water layer formation in the horizontal pipe.Experimental results have been obtained in stainless steel pipes of three different diameters (24.6mm; 30.8mm and 40.5mm) with white spindle oil N° 10 and water. They have been shown in the form of water layer maps.